Muscle Function In Low Back Pain: Is Bigger And Stronger What Matters? - Mahato, Niladri Kumar (Journal of Bangladesh Society of Physiologist, 2017)
The search for risk indicators for acute or chronic low back pain has been intensified in the last couple of decades. This review summarizes reports and reviews that have investigated the efficacy of predictive risk-factors in low back pain and offers clinicians an overview of the evidence that links the causal relationship between alterations in trunk muscle functional capacity (strength and endurance) and muscle morphology with low back pain (LBP). Primary research articles and reviews evaluating physiological properties of trunk muscles strength and endurance in back pain patients and in normal individuals were searched from the Medline and PubMed databases for this review to explore probable etiological predictors of back pain. The results show that though loss in muscle strength and endurance are commonly observed in patients with LBP, their role in forecasting an acute onset or in predicting chronicity of LBP has been unsatisfactory and equivocal. Attempting to find a single and clear-cut back pain predictor involving muscle strength, endurance may or muscle size may be challenging and information obtained only from one of these variables may not be adequate to explain the spectrum of LBP symptomatology in the patient in the clinical setting. Research indicates that suggesting a direct etiological relationship between weaker back muscles and low back pain may be a very simplistic. Similarly, strong back muscles do not offer guarantee against acute or chronic non-specific low back pain. Bangladesh Soc Physiol. 2017, June; 12(1): 41-51